A Interpretação de libras com o uso de novas tecnologias no ensino superior - Nascimento, Wendell Souza (Brasil, 2022)
The present research entitled “The Interpretation of Libras with the use of New Technologies in Higher Education”, aimed to investigate how the work of interpreting Libras is being carried out in different undergraduate courses in Higher Education as well as to know the contributions of the New Technologies in the daily life of professionals translators/interpreters of Libras, through the confrontation of the SARS-COVID-19 virus. It is a research with a qualitative approach, based on Minayo (2010). For the data collection, a semi-structured interview was carried out with 5 interpreters from a Higher Education institution in the Municipality of Parintins-AM, applied through the google forms platform, which is a viable and safe way to conduct the interviews. After organizing the data of the participating interpreters, we proceeded with the analysis based on the literature on which the theoretical framework was based. With contributions from Imbernóm (2010), Moran, Massetto and Behrens (2012), Quadros (2007) among others. From the analyzes developed, it was possible to conclude that the entire academic community needs to have knowledge about the deaf subject and their linguistic difference. In this way, the research achieved the expected objective, to understand how the work of interpreting Libras occurs in the learning of the deaf subject, mediated by technological resources, bringing elements that contribute to the process of inclusion of the deaf subject.